2020
DOI: 10.1097/aln.0000000000003390
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Exerts an Anti-inflammatory Effect via α2 Adrenoceptors to Prevent Lipopolysaccharide-induced Cognitive Decline in Mice

Abstract: Background Clinical studies have shown that dexmedetomidine ameliorates cognitive decline in both the postoperative and critical care settings. This study determined the mechanism(s) for the benefit provided by dexmedetomidine in a medical illness in mice induced by lipopolysaccharide. Methods Cognitive decline, peripheral and hippocampal inflammation, blood–brain barrier permeability, and inflammation resolution were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 45 publications
0
30
0
1
Order By: Relevance
“… Zhang et al (2018) found that sustained stimulation of β 2 and β 3 receptors increased the levels of TNF-α, IL-6, and IL-1β in the plasma and CSF, while microglia and astrocytes in the spinal cord were activated. A recent study suggested that α 2 -AR also participates in regulating neuroinflammation, and dexmedetomidine treatment prevents LPS-induced cognitive decline and neuroinflammation by inhibiting nuclear factor kappa B (NF-κB) through a pathway mediated by α 2 -AR ( Li et al, 2020 ). However, the specific pathophysiological mechanism by which LCNE regulates neuroinflammation is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“… Zhang et al (2018) found that sustained stimulation of β 2 and β 3 receptors increased the levels of TNF-α, IL-6, and IL-1β in the plasma and CSF, while microglia and astrocytes in the spinal cord were activated. A recent study suggested that α 2 -AR also participates in regulating neuroinflammation, and dexmedetomidine treatment prevents LPS-induced cognitive decline and neuroinflammation by inhibiting nuclear factor kappa B (NF-κB) through a pathway mediated by α 2 -AR ( Li et al, 2020 ). However, the specific pathophysiological mechanism by which LCNE regulates neuroinflammation is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Second, DEX has proven to have opioid-sparing properties, and pain is one of the most important risk factors for EA in children (1). Third, recent studies revealed that DEX might have antiinflammatory, organ-protective, and neuroprotective effects, which may play a key role in preventing EA (1,87,88).…”
Section: Discussionmentioning
confidence: 99%
“…As DEX displays an anti-inflammatory and neuroprotective property ( Li R. et al, 2020 ), we, thus, investigated whether DEX plays a role in the protection of neonatal rats from anti-inflammation and its possible mechanism. We found that consistent with the previous result, the rats in the Saline + LPS group showed significantly increased levels of IL-1β and TNF-α in the serum compared with the rats in the saline + saline group (IL-1β: 6,316.41 ± 896.03 vs. 38.81 ± 11.87, P < 0.01; TNF-α: 1,702.62 ± 118.48 vs. 36.53 ± 11.94, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%